Assessment of the Labor Market Information System (LMIS) in the Lao People’s Democratic Republic PDR - World Bank (Washington, DC, 2022)
The Lao People’s Democratic Republic (PDR) has made substantial progress in poverty reduction even though its resource-based development pattern has historically limited the impact of growth on poverty reduction. The objective of the assessment is to support the Ministry of Labor and Social Welfare (MOLSW) in their planned reforms of labor market institutions and systems in Lao; in particular by supporting investments in a comprehensive Labor Market Information System (LMIS) for improved jobseeker data collection and analytics, jobseeker profiling, and assignment to various employment support programs such as vocational trainings and job search assistance. The target audience of this report is the technical staff and management at the department levels as well as the policy makers at the MOLSW, Ministry of Planning and Investment (MPI) as well as the Ministry of Finance (MOF).